Relationship between parental attachment, peer attachment, problem focused strategy and stress among school-going adolescents in Akwa Ibom State, Nigeria - Abia, Edidiong Maurice (2021)
Despite a plethora of research that investigated parental attachment, peer attachment, problem-focused strategy and stress, there exists a variety of uninvestigated socio-cultural contexts. More so, empirical investigation has been very scanty with regards to the relationships among stress, parental and peer attachments, and problem focused strategy among school-going adolescents in Nigeria. The study was a cross-sectional survey which drew participants, using a purposive sampling technique, from the three senatorial zones of Akwa Ibom state in South-south Nigeria. Data were collected using standardized, reliable and valid measures of the study variables. Of the 372 school-going adolescents who participated in the study, 221 (59.4%) were females while 151 (40.6%) were males. Participants ages ranged from 10 to 18 years with a mean of 14.0 (SD = 3.97). Results showed that parental attachment (r = -.107, p<.05), peer attachment (r = -.190; p<.01) and problem-focused strategy (r = -.173; p<.01) were significantly associated with stress. Results also indicated that parental attachment, peer attachment, and problem-focused strategy significantly predicted stress.This means that the lower the parental attachment, peer attachment and problem-focused strategy, the more like the experience of stress.In terms of joint prediction, parental attachment, peer attachment, and problem focused strategy significantly predicted stress(R = .50; R2 = 0.25; p = .01). Peer attachment was found to be the strongest predictor of stress. Practically, the studyoffered parents/guardians, home managers and educational institutions useful suggestions on reducing and mitigating the effects of stress.Thefindings of the study and the conclusions portend beneficial implications to governments and policy makers. Stress reduction through healthy parental and peer attachment and adoption of problem-focused strategy can be enhancedby organizing school-based psycho-educational with focus on parental and peer attachment as well as problem-focused strategy.